Measurement of Serum Vitamin D Level and its association with Rheumatoid Arthritis, A prospective study at eastern region of Nepal. - Gupta, Mithilesh Kumar; Gupta, Pradeep Kumar; Panthee, Rajan (Birat Journal of Health Sciences, 2023)
Introduction: Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease characterized by synovitis. The etiology and pathogenesis of RA remain obscure and many factors may be associated with its pathogenesis. Recent findings support that low levels of serum Vitamin D is associated with an increased risk for the development of RA. Recently, the role of vitamin D deficiency in the pathogenesis of RA, as well as the relationship between vitamin D deficiency and the activity of RA has also been an area of interest for many researchers. Objectives: The objectives of this study is to analyse the vitamin D levels in RA patients and investigate the association between the serum levels of vitamin D and disease activity of RA patients from Eastern region of Nepal. Methodology: A prospective study was conducted at Birat Medical college teaching hospital, Tankisinwari from September 2022 to August 2023. A total of 150 patients, after fulfilling exclusion and inclusion criteria were enrolled with convenience sampling technique. A control group (n=97) of patients were also enrolled for comparison. After collection of all data, ANOVA test was used to compare continuous variables between control and vitamin D groups. Results: Vitamin D deficiency was found in 35 patients (23.3%), Vitamin D insufficiency found in 94 patients (62.6%), and is normal in only 21 patients (14%). Also patients with RA had significantly lower vitamin D levels in comparison to patients with control activity. The difference between these two groups was statistically significant (P<0.05). Conclusion: Our study finds a significant inverse relationship between blood vitamin D levels and RA activity. However, due to the small number of patients included in the current study, further research with a larger sample size is needed to gain a better understanding of the relationship between RA activity and vitamin D.